Pregnancy-Related Effects on Lamivudine Pharmacokinetics in a Population Study with 228 Women - Benaboud, Sihem (American Society for Microbiology, 2012)
The aim of this study was to describe lamivudine (3TC) pharmacokinetics (PK) in HIV-infected nonpregnant and pregnant women and their fetuses. Samples were collected according to therapeutic drug monitoring from 228 women treated with lamivudine and retrospectively analyzed by a population approach. The samples were also collected from cord blood and amniotic fluid at birth. Lamivudine pharmacokinetics were ascribed to an open two-compartment model with linear absorption and elimination. Mean population parameter estimates (intersubject variability) for women were an absorption rate constant of 1.04 h(−1), an elimination clearance rate of 23.6 (0.266) liters · h(−1), a central volume of distribution of 109 (0.897) liters, an intercompartmental clearance rate of 6.7 liters/h, and a peripheral volume of distribution of 129 liters. A fetal compartment was linked to maternal circulation by mother-to-cord (or fetus) and cord-to-mother rate constants of 0.463 h(−1) and 0.538 h(−1), respectively. The amniotic fluid compartment was connected to the fetal compartment with an elimination rate constant of 0.163 h(−1) and a fixed-constant swallowing flow. The placental transfer expressed as fetal-to-maternal area under the concentration-time curve (AUC) ratio was 0.86, and the lamivudine amniotic fluid accumulation, expressed as the amniotic fluid-to-fetal AUC ratio, was 2.9. Pregnant women had a 22% higher apparent clearance than nonpregnant and parturient women; however, this increase did not lead to subexposure and should not require a dosage adjustment.